Rationalizing Divine Scripture: Hasbi Ash-Shiddieqy’s Interpretation of Quranic Narratives on Prophetic Miracles and Earlier Communities - Amaliea Rizqi; Dwi Saputra, Ali Thaufan; Ansari, Miftach (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
This study explores the rational approach in Qur’anic interpretation by Hasbi Ash-Shiddieqy, as found in his work Tafsir Al-Qur’anul Majid an-Nur, particularly in relation to verses about prophetic miracles and stories of past nations. Traditionally, Qur’anic commentators have interpreted such verses by relying on classical reports, including Hadith and Israiliyat narratives. However, Hasbi offers an alternative, more rational and contextual approach. This research employs a qualitative method with a textual analysis of Hasbi’s tafsir. The study focuses on his interpretation of the miracles of Prophet Jesus (Ali ‘Imran: 49), the affliction of Prophet Ayyub (al-Anbiya’: 83 and Sad: 41), Prophet Abraham and the birds (Ali ‘Imran: 260), Prophet Sulaiman’s (Solomon) ability to understand the language of animals (al-Naml: 16–20), and the story of Uzair (al-Baqarah: 259). The findings reveal that Hasbi attempts to rationalize these verses through engagement with modern scientific perspectives, including references to medical science and interpretative deviations from literal meanings. Nevertheless, he also incorporates traditional narratives, including Israiliyyat, as supplementary material. The study concludes that Hasbi developed a model of interpretation that integrates rational reasoning with classical exegetical traditions, making his approach particularly relevant in contemporary academic discourse.